2022
DOI: 10.3390/microorganisms10091704
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Leishmaniasis in Sicily (Italy) from 2013 to 2021: One-Health Impact and Future Control Strategies

Abstract: Leishmaniasis is an important vector-borne disease that represents a serious public health problem, including in Sicily (Italy), which is considered an endemic area. We collected canine, feline and human data from 2013 to 2021 in Sicily, while entomological surveys were conducted only in 2013 and 2021. Overall, 23,794/74,349 (34.4%) of dogs and 274/4774 (11.8%) of cats were positive in one or more diagnostic tests. A total of 467 cases of human Leishmaniasis were reported, with 71% showing cutaneous and 29% vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 59 publications
3
2
0
Order By: Relevance
“…Our study confirmed the highest prevalence of FeL in the Sicily region in southern Italy, as reported by recent published studies [9,45,52]. This region has the highest endemicity for animal leishmaniosis and highest incidence of human infection among the Italian regions [5,45].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study confirmed the highest prevalence of FeL in the Sicily region in southern Italy, as reported by recent published studies [9,45,52]. This region has the highest endemicity for animal leishmaniosis and highest incidence of human infection among the Italian regions [5,45].…”
Section: Discussionsupporting
confidence: 92%
“…Our study confirmed the highest prevalence of FeL in the Sicily region in southern Italy, as reported by recent published studies [9,45,52]. This region has the highest endemicity for animal leishmaniosis and highest incidence of human infection among the Italian regions [5,45]. Originating from the Sicily region was a risk factor for seropositivity for antibodies against L. infantum, but not for qPCR positivity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding samples from Pantelleria Island, it should be noted that this island is characterized by ideal conditions to study leishmaniasis in a defined population of animals and in a circumscribed and central territory of the Mediterranean basin. Previous studies reported a Leishmaniasis prevalence of 27% in the dog population of the island, which is in line with the average prevalence in the Sicily region, indicative of an active circulation of the parasite in the island [ 12 , 42 ]. In this area, only 23.5% of canine clinical isolates/samples were associated with the G1 genotype while 70.6% were identified as the G6 genotype (390T/1831A).…”
Section: Discussionsupporting
confidence: 80%
“…The study by Moirano et al showed, during an 8-year period (2009–2016), 1126 cases of VL with a crude incidence rate (IR) of 2.43 cases per 10 6 person-years with 2 age peaks: the first in the age groups of 0–4 years (IR 7.63 cases) and the second in the age group of 65–74 years (IR: 2.79 cases) (Moirano et al ., 2022 ). The highest IR (16 cases per 10 6 person-years) was reported in the Agrigento province of Sicily; these data agree with a retrospective study of leishmaniasis conducted in Sicily from 2013 to 2021 that showed that the largest number of cases of human and canine leishmaniasis were from Agrigento (45.4 and 41.5%, respectively) (Bruno et al ., 2022 ; Moirano et al ., 2022 ). The changing epidemiologic landscape for leishmaniasis in Italy with the recognition of new endemic foci is further confirmed by the upsurge (observed since 2012) in VL and CL cases diagnosed in the Emilia-Romagna region (Varani et al ., 2013 ; Gaspari et al ., 2022 ).…”
Section: Symposium On the Italian Network On Ntdsmentioning
confidence: 99%